2013
DOI: 10.1002/lary.24474
|View full text |Cite
|
Sign up to set email alerts
|

Vibroplasty in mixed and conductive hearing loss: Comparison of different coupling methods

Abstract: Objectives/Hypothesis: To evaluate modified coupling techniques of the Vibrant Soundbridge system in patients with mixed and conductive hearing loss and to compare it with conventional vibroplasty.Study Design: Retrospective study. Methods: Two different groups were evaluated: 1) nine cases of conventional incus vibroplasty in comparison with 2) nine patients with modified coupling of the floating mass transducer. In the modified coupling approach, the vibrant floating mass transducer was attached to 1) the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
1
21
0
2
Order By: Relevance
“…These patients do not benefit from conventional hearing aids. The active middle ear implants bypass the middle ear ossicles, thereby providing a reliable hearing restoration strategy . The most advantageous positioning of FMT at the stapes superstructures or the RW include cases of mixed hearing loss, especially in cases where bone‐conduction transducers are insufficient due to the patient's bone conduction power limits.…”
Section: Discussionmentioning
confidence: 99%
“…These patients do not benefit from conventional hearing aids. The active middle ear implants bypass the middle ear ossicles, thereby providing a reliable hearing restoration strategy . The most advantageous positioning of FMT at the stapes superstructures or the RW include cases of mixed hearing loss, especially in cases where bone‐conduction transducers are insufficient due to the patient's bone conduction power limits.…”
Section: Discussionmentioning
confidence: 99%
“…An important group of patients are those with atresia of the external auditory canal. If these patients wanted to avoid a percutaneous solution, the only other implantable solution was an active middle ear implant, for example a Vibrant Soundbridge (MED‐EL, Innsbruck, Austria) . Recently, Frenzel et al have published a useful scoring system to rate the difficulty of such an operation in atretic temporal bones .…”
Section: Discussionmentioning
confidence: 99%
“…Originally, the floating mass transducer (FMT) was connected the to the long process of the incus . Alternative coupling approaches including the round, the oval window, or even the promontory bone extended the range of indications over recent years. Therefore, patients with mixed/conductive hearing loss could also be treated with this type of active middle ear implant .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, patients with mixed/conductive hearing loss could also be treated with this type of active middle ear implant. [1][2][3][4][5][6] To date, a few studies focused on long-term audiological or surgical outcomes. Maier et al 7 reported on audiological outcomes in 104 patients and 122 devices implanted in a single center.…”
Section: Introductionmentioning
confidence: 99%